Penerapan Prinsip Tadao Ando Pada Perancangan Pusat Kesehatan Mental di Kota Palu - khaerunnisa, khaerunnisa; Mutmainah, Mutmainah; Setiawan, A.; Syahrullah, M. Rachmat (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
The study was conducted to support the healing of survivors of mental health disorders in Central Sulawesi. Therefore, the Mental Health Center facilitates healing and recovery. Apart from that, the mental health center is also a forum for education about mental health disorders in order to raise awareness and understanding about the importance of maintaining mental health. This research method uses descriptive qualitative research methods, which are then processed using architectural design methods through the process of designing buildings, data collection, concept analysis and design. From the results of this analysis, the design concept and design of mental health centers in the city of Palu are produced. The result of this study is a Mental Health Center in Palu City with the application of Tadao Ando's design principles which will be able to accommodate the function of the building as a place for healing and education for the people of Palu City.